ANALISIS PENGARUH KONSERVATISME AKUNTANSI DAN STRUKTUR MODAL TERHADAP KINERJA KEUANGAN PERUSAHAAN - Zuhrotul Millah; Luhgiatno Luhgiatno; Panca Wahyuningsih (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2020)
The company's financial performance is an indicator of the company's success in generating profits. Conservatism is also closely related to the value of a company's assets because it includes a slowdown in revenue recognition leading to lower retained earnings and faster loss recognition. This study aims to analyze the effect of Accounting Conservatism and Capital Structure on Company Financial Performance on sub property, real estate and building construction service companies registered in May 2015-2017. In this study there are 26 data companies property, real estate and building construction with the number of observations for 3 years (2015-2017) as many as 78 research samples obtained by purposive sampling method. Data collection method is done through documentation study. The data analysis technique used is multiple regression analysis. The results of this study indicate that accounting conservatism has no effect on financial performance while capital structure has an effect on financial performance. The use of corporate debt will be able to reduce the amount of tax borne by the company, so that the reduced tax borne by the company will improve the company's performance in terms of profitability. Keywords : Accounting Conservatism; Capital Structure; Financial Performance